2017
DOI: 10.14411/eje.2017.027
|View full text |Cite
|
Sign up to set email alerts
|

Fitness traits of Drosophila melanogaster (Diptera: Drosophilidae) after long-term laboratory rearing on different diets

Abstract: Abstract. Nutrition is one of the most important environmental factors that infl uence the development and growth in Drosophila. The food composition strongly affects their reproduction, welfare and survival, so it is necessary for fl ies to search for a mixture of macronutrients that maximizes their fi tness. We have fi ve D. melanogaster strains, which were reared for 13 years on fi ve different substrates: standard cornmeal-agar-sugar-yeast medium and four substrates modifi ed by adding tomato, banana, carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…Therefore, the presence of SC (live or dry) in the juvenile diet tended to enhance copulation ability in either sex, depending on the diet treatment of the sex partner. These data again suggest that increased copulatory performances result from an adaptative process after many generations of adaptation on drySC-rich food in the laboratory, as reported for other diets 54,55 . The fact that SC-rich diet also induced enhanced reproductive behaviour suggests that the nutriments contained in both SC and dry SC yeasts participate in this adaptative process.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the presence of SC (live or dry) in the juvenile diet tended to enhance copulation ability in either sex, depending on the diet treatment of the sex partner. These data again suggest that increased copulatory performances result from an adaptative process after many generations of adaptation on drySC-rich food in the laboratory, as reported for other diets 54,55 . The fact that SC-rich diet also induced enhanced reproductive behaviour suggests that the nutriments contained in both SC and dry SC yeasts participate in this adaptative process.…”
Section: Discussionsupporting
confidence: 81%
“…These substrates significantly differ in C/N ratio (Trajković, Vujić, et al, 2017), as well as in antioxidant properties (Pavković-Lučić et al, 2017). From generation to generation, flies were maintained in glass 250 ml bottles under the optimal laboratory conditions for the species (25°C, 60% relative humidity, 300 lux, 12:12 h L: D photoperiod).…”
Section: Fly Strains and Maintenancementioning
confidence: 99%
“…In addition, we compared chemoprofile composition and major sex pheromones between virgin (results obtained in Pavković-Lučić et al, 2016) and recently mated flies belonging to those strains. In our previous investigations it has already been found that diet affected those strains on several levels: morphological variability, that is, wing morphology (Trajković et al, 2013(Trajković et al, , 2021, sex comb size and symmetry (Pavković-Lučić et al, 2013), as well as semiochemical profiles (Pavković-Lučić et al, 2016;, and fitness components (Trajković, Vujić, et al, 2017) were monitored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low intake of carbohydrates limits the energy reserve of an organism and can slow growth and regeneration, thereby altering survival and safety (Wheeler and Pi-Sunyer, 2008). Over the years, dietary modifications have been employed as a viable strategy to elucidate the mechanisms underlying certain adaptive traits in Drosophila melanogaster including reproductive, developmental as well as behavioural traits (Piper, 2017;Trajković et al, 2017). Furthermore, it has been established that the interplay between energy input and utilization is crucial to the determination of an organism's survival and reproduction and to a great extent the capacity of organism to adjust its developmental, physiological or behavioural response to varying environmental conditions.…”
Section: Introductionmentioning
confidence: 99%